2015
DOI: 10.1155/2015/817924
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Graphene Oxide Decorated Fe3O4@SiO2 Nanocomposites with Superior Adsorption Capacity and SERS Detection for Organic Dyes

Abstract: The fast detection and removal of organic dyes from contaminated water has become an urgent environmental issue due to their high toxicity, chemical stability, and low biodegradability. In this paper, we have developed graphene oxide decorated Fe3O4@SiO2(Fe3O4@SiO2-GO) as a novel adsorbent aiming at the rapid adsorption and trace analysis of organic dyes followed by surface enhanced Raman scattering (SERS). The structure and morphology of the nanocomposites were characterized by transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…2(a)) showed that only the MRHA has peaks at 602 and 1398 cm −1 which are related to the Fe-O bending and stretching vibration respectively [29,30]. Both for RHA and MRHA the peaks observed at 468, 798, 1103, 3145 cm −1 indicate the silica functional groups of C-Si-O, Si-H, Si-O-Si and -OH stretching respectively [29,31,32]. The N 2 adsorption-desorption isotherms of RHA and MRHA showed Type-IV isotherm with H3-type hysteresis (Fig.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…2(a)) showed that only the MRHA has peaks at 602 and 1398 cm −1 which are related to the Fe-O bending and stretching vibration respectively [29,30]. Both for RHA and MRHA the peaks observed at 468, 798, 1103, 3145 cm −1 indicate the silica functional groups of C-Si-O, Si-H, Si-O-Si and -OH stretching respectively [29,31,32]. The N 2 adsorption-desorption isotherms of RHA and MRHA showed Type-IV isotherm with H3-type hysteresis (Fig.…”
Section: Characterizationmentioning
confidence: 99%
“…MRHA has a higher surface area and mesopore volume (Table S1) compared to RHA possibly caused by the presence of ferrite nanoparticles which is known to have a large surface area and pore volume [36]. Primarily, the higher mesopore volume of MRHA could be due to ferrite particles growing uniformly along the silica framework creating more mesopores [37] and functionalized iron oxide also has reportedly high inherent mesopore volume [29,30,37].…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained SiO 2 @CoFe 2 O 4 nanocomposites were then functionalized with amino groups by adding APTES as a precursor material [39]. Herein, 0.5 g of SiO 2 @CoFe 2 O 4 nanocomposites were added to the 50 mL of toluene, followed by adding 4 mL of APTES.…”
Section: Synthesis Of Amino-functionalized Sio 2 @Cofe 2 O 4 Onto Go mentioning
confidence: 99%
“…For its good electrochemical performance, it is useful in energy storage applications [22] such as in lithium-ion batteries [23]. Fe3O4/rGO nanocomposites can be used as photocatalytic material [24,25], for reducing heavy metals such as Cu +2 , Zn +2 , Ni +2 ions [26], Cr -2 [27][28][29][30], Pb 2+ [27,30], detecting Cd +2 [31] ions, degradation of phenol, as an antibacterial [25], for biosensing [31], and as an absorbent for removing dyes in aqueous solutions [32][33][34]. It has the potential to be used in a sensor to detect the presence of arsenic in mineral water [35,36], and wastewater treatment [37].…”
Section: Introductionmentioning
confidence: 99%